Biomimetic ion nanochannels for sensing umami substances. (March 2022) - Li, Mingyang; Zhang, Ninglong; Cui, Zhiyong; Wang, Wenli; Wang, Cunli; Wang, Dongdong; Li, Minmin; Lu, Wenqi; Qing, Guangyan; Liu, Yuan
Abstract: Umami is one of the basic taste sensing, and represents the recognition of N-containing compounds capable of evaluating the nutritious contents of food. Although several sensors have been developed, the assessment of umami intensity remains challenging due to the limitations of sensor specificity, sensitivity, and performance stability. Here we present a biomimetic conical nanochannels system integrated with Venus flytrap (VFT) domain from human umami receptor T1R1 subunit to meet the concern. By taking advantage of sensitive transmembrane ionic flux change, the functional nanochannels could precisely distinguish umami substances from other tastants. Detailed mechanism analysis reveals that specific binding between T1R1 and umami substances triggers local conformation change and surface charge redistribution of the protein, which modulates the ionic current. This study initiates the application of nanochannel device in taste perception, which could help to disclose umami perception mechanism and screen new umami substances.